Innovative Approaches to Cloud-Based Accounting Information Systems: Integrating AI, Blockchain, and IoT - Mukhsin, Mukhsin; Renaldo, Nicholas; Junaedi, Achmad Tavip; Veronica, Kristy; Cecilia, Cecilia (International Conference on Business Management and Accounting, 2023)
A cloud-based accounting information system (AIS) leverages cloud computing technology to manage financial data and processes. This research aims to explore innovative aspects in developing a cloud-based AIS to address contemporary business needs and technological advancements. The primary objectives are to design a cloud-based AIS incorporating cutting-edge technologies, evaluate the effectiveness of these innovations in enhancing system performance and user experience, and identify challenges and best practices in implementing a cloud-based AIS. The study's contributions are twofold: academically, it provides a comprehensive framework for developing innovative cloud-based AISs; practically, it offers a solution for businesses seeking to enhance their accounting processes through advanced technology. Proposed innovations include AI-powered financial analysis, blockchain-based security, IoT-integrated expense management, and advanced data visualization. A mixed-methods approach will be employed, combining quantitative and qualitative data collection and analysis. The research methodology involves system design, prototyping, technology integration, development, testing, deployment, evaluation, and maintenance. The algorithm for building the cloud-based AIS includes steps such as requirement analysis, system design, prototyping, technology integration, development, testing, deployment, evaluation, and maintenance. The discussion highlights the importance of each step in ensuring the system's success, focusing on user-centric design, scalability, and advanced technological integration. The research concludes that developing a cloud-based AIS with novel features has the potential to transform financial management practices, providing a more efficient, secure, and user-friendly accounting solution. Future research will address challenges related to data privacy and security, user adoption, scalability, and interoperability.